FROM SHORT STORY TO SHORT FILM: LOCALIZING A TEMPORARY MATTER IN INTERLUDE AND THE LOTTERY IN BLACK BOX - Muhammad Rizal; Tarangga Widyadhana; Yasmin Hasna Dzakiyyah; Isnan Waluyo (FRASA: ENGLISH EDUCATION AND LITERATURE JOURNAL, 2026)
World literature adaptation into short films by university students creates a reflective space for literary education and film production sensitive to local contexts. This study examines how students of the English Literature program at Universitas Islam Negeri Raden Mas Said Surakarta adapted two short stories, A Temporary Matter and The Lottery, into short films that embed Indonesian local wisdom. The research was conducted in the English Indie Movie Production course as a direct application of adaptation theory. A descriptive-analytical method was employed, with data collected through documentation, and textual and visual notes. The analysis draws on four sources: the original short stories, the short films uploaded on YouTube, Instagram posts used to promote local narratives, and audience responses. Linda Hutcheon’s adaptation theory (2013) is used to interpret the process of transferring texts into film. The study reveals creative and contextual adaptation practices by students and demonstrates how media production-based learning fosters active engagement. Findings show that students successfully reinterpret universal issues from classic short stories through the lens of local culture.